Earnings behaviour of financially distressed firms: the role of institutional ownership - Trigeorgis, Lenos; Lambertides, Neophytos; Charitou, Andreas G. (My University, 2007)
Using a sample of 859 U.S. bankruptcy-filing firms over the period 1986-2004, we examine the earnings behaviour of managers during the distressed period by looking at sources of abnormal accruals prior to the bankruptcy-filing year. Results show that managers of highly distressed firms shift earnings downwards prior to the bankruptcy filing. We test and provide evidence in support of two potential contributing factors. First, top-level management turnover among distressed firms leads new managers to earnings bath choices during the distressed period. Second, qualified audit opinions exert pressure on managers to follow more conservative earnings behaviour during the distressed period. Evidence is also provided that the management of distressed firms with lower (higher) institutional ownership has greater (lesser) tendency to manage earnings downwards. Results also show that higher institutional ownership mitigates the negative abnormal returns of firms with top management turnover. To the authors' knowledge, this is the first study that attempts to examine whether institutional ownership relates to market reaction in conjunction with a top management turnover or a qualified audit opinion during the distressed period. Prior studies focused on the investigation of earnings management or institutional ownership (separately) during the distressed period, but did not examine if the effect of institutional ownership on earnings behaviour also influences subsequent returns. Thus, the results of this study should be of interest to analysts, standard setters and regulatory bodies since our results show that management turnover, qualified audit opinions and firm governance mechanisms affect the quality of earnings and the level of abnormal returns
Keywords: Bankruptcy; Bankruptcy--Accounting; Financials